The Adaptability of Passion Scale for Tertiary Students in Japanese Online Courses in Indonesia - Kaluge, Teresa Angelina; Hadiutomo, Dwi Anggoro; Kaluge, Laurens (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aimed at examining the opportunities for adapting the passion scale to Japanese literature students who carried out the online learning process in Indonesia. This study used quantitative covariance structure design as the application of item response theory. From a sample of 148 undergraduate students, originally from three different courses. Data were obtained by filling out a virtual questionnaire which adapted from the original Dual Model Passion scale. Since this scale had been developed abroad, the data were analysed quantitatively using confirmatory factor analysis and regression, this study replicated the similar analysis while examined passion by using five criteria such as time, like, value, passion, identity as used in the previous development process. In addition, the criteria for student characteristics (gender and age) and conditions (first year vs. advanced year) in attending online lectures by observing the relationship between the two main dimensions of passion). The results showed that first year students tend to have a higher harmonious passion (HP), while second year students had a higher obsessive passion (OP). In conclusion, several things needed to be considered by researchers and lecturers at tertiary institutions such as course and student characteristics, so that students' passion remained good even though they had to study online during the outbreak of the Covid-19.